Data Mining Grouping Areas Of Diarrhea Disease In The City Medan Using K-Means (Clustering) Algorithm In Service Environment In Medan City - Borkat parulian pohan (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2023)
Diarrhea is a contagious disease and is characterized by symptoms such as changes in the shape and consistency of the stool from becoming soft to liquefying and an increase in the frequency of defecation more than usual accompanied by vomiting, thus causing sufferers to experience a lack of fluids in the body or dehydration which in In the end, if you don't get help immediately it can cause seriousness and even death. Diarrhea can attack all ages with symptoms such as frequent bowel movements with a liquid or watery stool consistency, signs and symptoms of dehydration, fever, vomiting, anorexia, weakness, paleness, changes in vital signs (rapid pulse and breathing), urine output. decreased or absent. Of the 20 data grouping of diarrheal disease areas using the clustering method with the k-means algorithm, 3 groups were obtained, where the most cluster members were in cluster 1 with a total of 11 data centered on centroids 2, 5, 3, namely data on the spread of diarrhea in 6-10 sub-districts, the number 15,000-20,000 sufferers with sporadic distribution status.Keywords: Data Mining, Medan City Environment Service, K-means algorithm